A Division of Labor Perspective on Mothers Who Accompany Their Children's Study—A Case Study of Student Guardianship among M Town's Working Families. (2nd January 2020) - Yunxia, Fan; Xinrong, Zheng
Abstract : In modern society, female parents from different strata are involved in the process of constructing their motherhood through education. But mothers of different social classes have different ways of acting. Amid increasingly fierce educational competition, the mothers of ordinary working families move into the school neighborhood to look after their children as the college entrance examination (gaokao) approaches, and construct their "student guardian motherhood" status through their task of accompanying their children's study. This paper takes as its subject mothers as student guardians in M Town, a typical gaokao community, providing a structural analysis of the features of such mothers' educational labor and production relations from the perspective of gender and class. Seen in the light of the family's gendered division of labor, the educational work of student guardian mothers is a new form of housework. In terms of the content of its division of labor, the student guardian work of mothers dedicated to their children's well-being counts as "low-end" work, an overflow from links in the division of labor in school education. On the one hand, due to their lack of cultural capital, the relationship between parents and schools is one of "accompanying" and "submission." On the other, these parents consciously keep their distance from "quality education" and form an organic compound with the schools' efficient exam-centered education. The traditional Chinese idea of "hoping one's sons become dragons" [achieve greatness] and the modern "child-centered" concept of nurturing jointly shape the image of student guardian mothers who work as service-oriented mothers in tandem with school education. The function of student guardians is not only the educational labor of "looking after the children" enjoined on middle- and lower-class female parents by the current division of education and social labor, but also an active and rational action strategy adopted by working class Chinese mothers striving for their children's academic success.